Gastroprotective effect of vanillic acid against ethanol-induced gastric injury in rats: involvement of the NF-κB signalling and anti-apoptosis role - ERCAN, FERİHA (My University, 2024)
Background: Vanillic acid (VA; 4-hydroxy-3-methoxybenzoic acid) is a flavouring agent found in various natural sources such as olives, fruits, and green tea. While VA exhibits numerous pharmacological effects, its potential protective effects against gastric injury warrants further investigation. Therefore, the primary objective of this study is to elucidate investigate the gastroprotective properties of VA against ethanol-induced gastric injury. Methods and results: Rats were orally administered either saline or VA at different doses (50, 100, and 200 mg/kg/day), with omeprazole (20 mg/kg) serving as a positive control, for fourteen consecutive days before ethanol administration. Blood and gastric tissue samples were collected one hour after ethanol administration for biochemical, molecular, and histological analyses. Pre-treatment with VA before ulcer induction alleviated both macroscopic and microscopic damage. It also increased antioxidant glutathione levels and decreased malondialdehyde and myeloperoxidase activity, along with reducing inflammatory markers such as tumour necrosis factor (TNF)-α, interleukin (IL)-6, and nuclear factor kappa B (NF-κB). Additionally, VA pre-treatment reversed the elevation of Bax mRNA expression and gastric caspase-3 levels induced by gastric damage. It also mitigated the reduction in Bcl-2 mRNA expression. Conclusion: These findings suggest that VA exerts protective effects against ethanol-induced gastric injury in rats. It achieves this by augmenting gastric antioxidant capacity and mitigating oxidative, inflammatory, and apoptotic damage.
Keywords: Tıp; Dahili Tıp Bilimleri; Tıbbi Genetik; Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Sağlık Bilimleri; Temel Bilimler; Medicine; Internal Medicine Sciences; Medical Genetics; Life Sciences; Molecular Biology and Genetics; Health Sciences; Natural Sciences; Yaşam Bilimleri (LIFE); GENETİK VE KALITIM; Life Sciences (LIFE); MOLECULAR BIOLOGY & GENETICS; GENETICS & HEREDITY; Moleküler Biyoloji; Genetik; Molecular Biology; Genetics; Apoptosis; Gastric ulcer; Inflammation; Oxidative damage; Vanillic acid